Facile preparation of lightweight PE/PVDF/Fe3O4/CNTs nanocomposite foams with high conductivity for efficient electromagnetic interference shielding. (December 2020) - Zhao, Yishen; Hou, Junji; Bai, Zhongyi; Yang, Yang; Guo, Xiaoqin; Cheng, Haoran; Zhao, Zongshen; Zhang, Xiaoli; Chen, Jingbo; Shen, Changyu
Abstract: Light-weight Polyethylene/Poly(vinylidene fluoride)/Fe3 O4 /Carbon nanotubes (PE/PVDF/Fe3 O4 /CNTs) nanocomposite foams with efficient electromagnetic interference (EMI) shielding performance were prepared using green processing methods of melt blending and supercritical CO2 foaming. The microwave- absorbing ability of the PE/PVDF/Fe3 O4 /CNTs nanocomposite foams were significantly improved. Moreover, due to the selective dispersion of Fe3 O4 and CNTs in the PVDF and PE matrix, respectively, CNTs directionally arranged in the cell wall during the foaming, leading to a high electric conductivity to improve the electromagnetic interference shielding effectiveness (EMI SE) through dielectric loss and polarization loss. The produced PE/PVDF/Fe3 O4 -10CNTs foam with a density of 0.9 g/cm 3 and a thickness of 2.6 mm, exhibited a higher electrical conductivity of 0.25 S/cm. The outstanding total EMI SE of 26 dB (the corresponding specific EMI SE was 110 dB cm 2 /g), measured across the Ku-band frequency region, was obtained. This forming strategy has potential industrial application and large-scale EMI shielding materials producing guidance.